Applications of gratings - Li, Xinyi (2016)
Gratings are fundamental and important elements in optical metrology. Our particular interest involves two applications of gratings which are optical spectrometer and three-dimensional (3D) profilometer. An one-layer thin film thickness measurement system is established based on spectrometer, in which the deflection is produced by diffraction in a diffraction grating. A calculation method derived from thin film interference principle is applied to postprocessing. As the second important application of grating, 3D profilometer combines the grating theory with illumination technique, and is used for surface measurement. In other part of this project, a 3D profilometer is designed using Digital Light Processing (DLP) fringe projector and CCD camera. Moreover, a few attempts to measure the different types of specimens have already been made with this 3D profilometer to identify what effects would be induced by diffusive and shiny surface, dark and bright environment, black and white color of objects, and polarizer.